Muscular and Skeletal Changes in Cervical Dysphonic in Women - Menoncin, Laiza Carine Maia; Jurkiewicz, Ari Leon; Silvério, Kelly Cristina A.; Camargo, Paulo Monteiro; Wolff, Nathália Martii Monti (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: The vocal and neck are associated with the presence of tension and cervical muscle contraction. These disorders compromise the vocal tract and musculoskeletal cervical region and, thus, can cause muscle shortening, pain and fatigue in the neck and shoulder girdle.Objective: To evaluate and identify cervical abnormalities in women with vocal disorders, and neck pains comparing them to women without vocal complaints independent of the neck.Method: This prospective study of 32 subjects studied in the dysphonic group and 18 subjects in the control group, aged between 25 and 55 year old female. The subjects underwent assessments, ENT, orthopedic, physical therapy and voice recording.Results: At Rx cervical region more patients in the control group had this normal, however, with regard to the reduction of spaces interdiscal dysphonic patients prevailed. Furthermore, postural assessment, the kyphosis of the 1st thoracic vertebra occurred in 77.0% of non-dysphonic group (p = 0.0091), while cervical rotation was present in 83% of control (p = 0.0051).Conclusion: Significant cervical abnormalities in both groups, but cannot be inferred that the changes are directly related to dysphonia.
Keywords: voice disorders; neck pain; posture